A novel approach to determining augmented bone volume in intraoral bone block augmentation using an intraoral scanner: an in vitro study - Bouffleur, Frederic; Kalchthaler, Lukas; Kühle, Reinald; Büsch, Christopher; Ristow, Oliver; Engel, Michael; Freudlsperger, Christian; Hoffmann, Jürgen; Mertens, Christian (International journal of implant dentistry, 2023)
Introduction: Bone augmentation procedures are established tools for reshaping the alveolar ridge and increasing bone volume. Different approaches are being used to measure postoperative bone volume gain. This study aimed to develop an objective and automated volume measurement tool equally as precise as manual slice-by-slice annotation. Materials and methods: To evaluate the proposed workflow, we performed an in vitro study with 20 pig mandibles that were grafted using three different grafting techniques—autogenous full block, split block bone and shell augmentation. The pig jaws were scanned pre- and postoperatively using an intraoral scanner. The resulting surface files (baseline, full block, split block, shell) were processed using the new volume-measuring workflow as well as using manual slice-by-slice annotation at baseline (t0) and at 6 months (t1) using the same population. Two TOSTs (Test of One-Sided Significance) and NHSTs (Null Hypothesis Significance Test) were used to compare the two workflows. The intra-rater reliability between t0 and t1 was determined using intraclass correlation coefficients. Results: The mean difference for the full block augmentation technique was − 0.015 cm3 (p < 0.001); for the split block technique, it was − 0.034 cm3 p = 0.01, and for the shell technique, it was − 0.042 cm3. All results were statistically not different from zero and statistically equivalent to zero. The results also showed an excellent absolute intra-rater agreement.Conclusions: The semiautomatic volume measurement established in this article achieves comparable results to manual slice-by-slice measuring in determining volumes on STL files generated by intraoral scanners and shows an excellent intra-rater reliability.
Veröffentlicht: 05. September 2023
Gesehen am 24.10.2023